2009
DOI: 10.17221/384-pse
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacteria from paddy fields in Iran as a biofertilizer in rice plants

Abstract: In this research cyanobacteria (Blue-Green Algae, BGA) were isolated, identified, multiplied and used as an inoculum in pot rice experiment. The pH, moisture and algal population were measured in four seasons. The highest and lowest pH (6.7, 6.2), moisture of soil (43%, 34%) and algal population (12, 20 Colony-Forming Units/50 ml on A and B medium and 4, 5 Colony-Forming Units/50 ml on A and B medium) were recorded in spring and winter, respectively. The only heterocystous cyanobacteria were found in soil samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(64 citation statements)
references
References 16 publications
(14 reference statements)
3
58
0
3
Order By: Relevance
“…These approaches should aim at developing a more efficient association between rice and diazotrophs by creating relationship between selected diazotrophs and rice. The experiment on non-leguminous crops with diazotrophic bacteria has been studied for many years with the expectation that these bacteria would fix dinitrogen gas and provide combined nitrogen to the plant for enhanced crop production (Saadatnia and Riahi, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…These approaches should aim at developing a more efficient association between rice and diazotrophs by creating relationship between selected diazotrophs and rice. The experiment on non-leguminous crops with diazotrophic bacteria has been studied for many years with the expectation that these bacteria would fix dinitrogen gas and provide combined nitrogen to the plant for enhanced crop production (Saadatnia and Riahi, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Cyanobacteria and green algae can play a crucial role in plant and soil fertility as nitrogen-fixing microorganisms and producers of several natural substances positively affecting growth. Thus, recently around the world, a considerable progress took a place in the development of cyanobacteria and green algae-based biofertilizer technology (Saadatnia and Riahi 2009). Proper foliar biofertilization with cyanobacteria and green algae may allow limit markedly doses of chemical fertilizers by as much as 50%, without significant reduction of growth and biomass yield of willow.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced growth of willow plants could be also caused by the ability of the blue-green algae to convert complex nutrients into simple ones available for plants (Sahu et al 2012) and to increase water-holding capacity through their jelly structure (Roger and Reynaud 1982). It might be also improved by the use of dead cyanobacteria as a fertilizer reducing soil salinity (Saadatnia and Riahi 2009). Treatment with cyanobacteria could also increase the phosphate content in soil by excretion of organic acids (Wilson 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In 1936, De first suggested that bluegreen algae could be used as bio-fertilizer in rice fields and can increase the fertility of the soil, and then he found that the algae bio-fertilizer can keep high production for rice in the absence of other fertilizer [21]. This result aroused the interest of many foreign scientists to blue-green algae as a fertilizer in the rice field and then more and more research on blue-green algae fertilizer increasing grain yield have been published, not only in India [22][23][24][25][26][27][28] but also in Japan [29], Philippines [30], the Iran [31], and other rice-growing countries. Watanabe [32] used the blue-green algae as a fertilizer in about 40 rice varieties in various parts of Japan and noted that an average increase in the fourth year in rice yield was 2%, 8%, 15% and 19.5%, respectively.…”
Section: The Progress Of Algae Bio-fertilizer In the Worldmentioning
confidence: 99%
“…In this regard, Iran scholar did a comprehensive work. They used blue-green algae as a bio-fertilizer for rice plants in pot experiment, the results shows that plant height increased 53%; roots length increased 66%; fresh leaf and stem weigh increased 58%; fresh root weight increased 80%; dry leaf and stem weight increased 125%; dry root weight increased 150% [31].…”
Section: The Progress Of Algae Bio-fertilizer In the Worldmentioning
confidence: 99%